Benang Merah Huffaz di Indonesia Studi Penelitian Biografi Huffaz - Khoeron, Mohamad (SUHUF, 2011)
Over the past two years, the Committee for the Checking of the Holy Qur'an (Lajnah Pentashihan Mushaf Al-Qur’an), Jakarta has carried out biographical research on huffaz (those who have learnt the Qur’an by the heart) in Indonesia. This article will attempt to draw out the key linkages from that research, and will also try to trace the role and position of the huffaz in preserving the traditions and the values of Islamic boarding schools (pesantren). The experience of these guardians of the Qur'an as documented in this research reflects their persistence, patience and love for practising the teachings of the Qur’an, and it from these qualities that religious students and huffaz emerge. Their role in helping to educate the people of the nation is continuously being developed, based on a sincere determination to produce people with a Qur'anic orientation.